2019
DOI: 10.1002/aoc.5306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nonplanar bipyridyls bridged by disilane and disiloxane and their phosphorescent copper complexes

Abstract: Disilane‐ and disiloxane‐bridged bipyridyls (DSBPy and DSOBPy) were prepared and their optical properties were investigated in comparison with those of previously reported monosilane‐ and monogermane‐bridged counterparts. The UV–visible absorption and photoluminescence bands of DSBPy and DSOBPy were blue‐shifted as a result of elongation of the bridging units from monosilane and monogermane to disilane and disiloxane, likely due to the enhanced twisting of the bipyridyl units. Phosphorescent complexes DSBPy–Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In 2020, Ohshita and co-workers used disilane- and disiloxane-bridged bipyridines to prepare the copper­(I) coordination polymers, DSBPyCu ( 29 ) and DSOBPyCu ( 30 ) (Figure a) . The X-ray crystal structures of the coordination polymers showed that [Cu 2 I 2 (PPh 3 ) 2 ] fragments were linked by bridging bipyridine ligands to form an extended polymeric structure, as shown in Figure b.…”
Section: Copper(i) Coordination Polymers For Oledsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2020, Ohshita and co-workers used disilane- and disiloxane-bridged bipyridines to prepare the copper­(I) coordination polymers, DSBPyCu ( 29 ) and DSOBPyCu ( 30 ) (Figure a) . The X-ray crystal structures of the coordination polymers showed that [Cu 2 I 2 (PPh 3 ) 2 ] fragments were linked by bridging bipyridine ligands to form an extended polymeric structure, as shown in Figure b.…”
Section: Copper(i) Coordination Polymers For Oledsmentioning
confidence: 99%
“…The X-ray crystal structures of the coordination polymers showed that [Cu 2 I 2 (PPh 3 ) 2 ] fragments were linked by bridging bipyridine ligands to form an extended polymeric structure, as shown in Figure b. The bipyridine moieties showed moderate twisting with C–C–C–C dihedral angles of 38.47–48.56°, and there were no observable intermolecular interactions in the packing of both compounds . As a result, the coordination polymers had a low tendency to form aggregates in the solid state, rendering them readily processable and, hence, suitable for OLED applications.…”
Section: Copper(i) Coordination Polymers For Oledsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] We also demonstrated that similar disilane-and disiloxane-bridged bipyridyl copper complexes were useful as phosphorescent organic light emitting diode (OLED) materials. [15] In the present work, we prepared dipyridinostannole DPySn1 (Scheme 1c, E=Sn, R 1 =Ph) as the first example of Sn-bridged bipyridyl and studied its optical properties in comparison with those of DPyS1 and DPyG1 with the same phenyl substituents, [11] to examine the effects of the bridging element. Copper complexes of DPyS1 and DPySn1 were also prepared and their optical properties were investigated in comparison with those of DPyG1.…”
Section: Introductionmentioning
confidence: 99%